System Dynamics in Distance Education and a Call to Develop a Standard Model - Shaffer, Steven C. (International Review of Research in Open and Distributed Learning, 2005)
This paper describes systems dynamics, reviews the literature of uses of systems concepts in distance education (DE), presents a preliminary model, and ends in a call to researchers to contribute to the building of a standard model of DE.